2018
DOI: 10.5603/fhc.a2018.0012
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in porcine intrahepatic sympathetic nerves after bisphenol A administration

Abstract: Introduction. Bisphenol A (BPA) is used in the chemical industry for manufacturing plastics which are used as food packaging. Data indicate that BPA is released from such products and is widely present in the environment and the human body. So far, the EFSA and the US FDA have determined "safe" BPA oral exposure levels, and a large amount of data indicates that BPA is harmful even at low-doses. Our previously performed analyses concerning BPA exposure demonstrated the impact of this substance on parasympatheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…Hypertensive effect of BPA exposure may be associated with altered autonomic nerves activity and/or expression of components of the renin-angiotensin system (RAS). Thoene et al (2018) demonstrated an increase in the number of sympathetic fibers in the liver in response to 50 µg kg −1 day −1 BPA exposure, the same dose used in the present study. However, conflicting data have been reported for the autonomic control of heart rate and an increased and attenuated parasympathetic tone has been suggested (Pant et al, 2012;Belcher et al, 2015).…”
Section: Discussionsupporting
confidence: 71%
“…Hypertensive effect of BPA exposure may be associated with altered autonomic nerves activity and/or expression of components of the renin-angiotensin system (RAS). Thoene et al (2018) demonstrated an increase in the number of sympathetic fibers in the liver in response to 50 µg kg −1 day −1 BPA exposure, the same dose used in the present study. However, conflicting data have been reported for the autonomic control of heart rate and an increased and attenuated parasympathetic tone has been suggested (Pant et al, 2012;Belcher et al, 2015).…”
Section: Discussionsupporting
confidence: 71%
“…Of course, BPA affects also other internal organs, including, among others, the liver [62], heart [63], endocrine glands [64], kidneys [65] and lungs [66], leading to disturbances in their functioning [43,44]. In turn, epidemiological studies on human population have shown correlation between the degree of exposure to BPA and risk of obesity, diabetes, hypertension, cancer and many other pathological processes [67,68].…”
Section: Species Localization Referencesmentioning
confidence: 99%
“…One of the most interesting aspects of the impact of BPA on the uterus is connected with the influence of this substance on the nervous system. Although it is known that neuronal tissue is sensitive to BPA and changes caused by this substance have been observed in various parts in both the central and peripheral nervous systems [ 25 , 26 ], these changes consist of disturbances in the development of dendrites and axons, changes in synaptogenesis, abnormalities in intraneuronal calcium ion transport, changes in neurochemical characterization of neuronal cells and nerve fibers, and disturbances in higher neuronal functions, including memory and learning [ 27 ]. Moreover, some investigations connect a high degree of exposure to BPA with neurodegenerative disorders, such as Alzheimer’s or Parkinson’s diseases [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%